Improvement of speed and strength qualities of football players at the stage of sports specialization - Bedarkov K.I. ,; Shilko V.G. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to develop test tasks that determine the level of speed and strength qualities of young football players. Methods and structure of the study. Two groups of football players took part in the pedagogical experiment: 12–13 and 14 years old. Data analysis was carried out using intragroup and intergroup indicators. The evaluation coefficient made it possible to compare the statistical set of measurement results of various physical quantities in their corresponding physical units. Results and conclusions. The proposed test tasks allow us to identify the level of development of speed-strength qualities. To increase the effectiveness of the educational and training process, focused on the development of speed and strength qualities, it is necessary to differentiate physical activity based on taking into account the individual characteristics of football players aged 12-14 years.